2003
DOI: 10.1103/physrevlett.91.043001
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Trielectronic Recombination in Be-like Cl Ions

Abstract: Recombination involving the core excitation of two electrons, which may be termed trielectronic recombination, has been experimentally identified for the first time. Using Cl13+ ions circulating in the TSR heavy-ion storage ring, we have observed surprisingly strong low-energy trielectronic recombination resonances, comparable to the dielectronic process. At higher electron-ion collision energies, trielectronic recombination is suppressed due to the autoionization of the triply excited intermediate state into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 13 publications
3
33
0
Order By: Relevance
“…The MBQC statistical theory quantitatively explains the discrepancy as being due to a very dense spectrum of compound resonances: multiply excited, strongly mixed, chaotic many-electron eigenstates. Note that this situation is distinct from trielectronic recombination (i.e., via resonances with three excited electrons) that has been experimentally observed in Be-like ions (N 3+ , O 4+ , Cl 13+ ) [37,38]. In these systems electron capture into a Rydberg state was accompanied by simultaneous 2s 2 → 2p 2 promotions.…”
Section: Theorymentioning
confidence: 97%
“…The MBQC statistical theory quantitatively explains the discrepancy as being due to a very dense spectrum of compound resonances: multiply excited, strongly mixed, chaotic many-electron eigenstates. Note that this situation is distinct from trielectronic recombination (i.e., via resonances with three excited electrons) that has been experimentally observed in Be-like ions (N 3+ , O 4+ , Cl 13+ ) [37,38]. In these systems electron capture into a Rydberg state was accompanied by simultaneous 2s 2 → 2p 2 promotions.…”
Section: Theorymentioning
confidence: 97%
“…[12][13][14]). In our previous experiments at electron beam ion traps (EBIT), we found that the higher-order recombination process can also lead to far more energetic inter-shell excitations [10,11] with a rather large contribution.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to radiative recombination (RR) and DR, a third resonant recombination channel, called trielectronic recombination (TR) is possible in Be-like ions. In this process, two electrons from the 2s state are excited to 2p state during the attachment of a free electron to a certain nl Rydberg state, forming a triply excited state (Schnell et al 2003;Fogle et al 2005). This occurs because of the strong mixing between the 2s 2 and 2p 2 configurations and the low excitation energy of the two 2s electrons (Schnell et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In this process, two electrons from the 2s state are excited to 2p state during the attachment of a free electron to a certain nl Rydberg state, forming a triply excited state (Schnell et al 2003;Fogle et al 2005). This occurs because of the strong mixing between the 2s 2 and 2p 2 configurations and the low excitation energy of the two 2s electrons (Schnell et al 2003). Throughout this paper, we use the convention of identifying the charge state prior to recombination.…”
Section: Introductionmentioning
confidence: 99%